Advances in topiramate as prophylactic treatment for migraine. Issue 10 (2nd September 2021) - Hu, Chuan; Zhang, Yixin; Tan, Ge
Abstract: It is well‐known that topiramate as a kind of antiepileptic drug has been proved effective for migraine prevention in North America and Europe. However, topiramate is still viewed as an off‐label medication for migraine treatment in China, partly because of the limited evidence in Chinese patients. We summarize the effects of topiramate on the frequency, severity, quality‐of‐life, and adverse event among migraine patients, including children and adolescent in this review, so as to provide reference for Chinese doctors. Abstract :